1997
DOI: 10.1128/aem.63.2.414-419.1997
|View full text |Cite
|
Sign up to set email alerts
|

An aminotransferase from Lactococcus lactis initiates conversion of amino acids to cheese flavor compounds

Abstract: The enzymatic degradation of amino acids in cheese is believed to generate aroma compounds and therefore to be involved in the complex process of cheese flavor development. In lactococci, transamination is the first step in the degradation of aromatic and branched-chain amino acids which are precursors of aroma compounds. Here, the major aromatic amino acid aminotransferase of a Lactococcus lactis subsp. cremoris strain was purified and characterized. The enzyme transaminates the aromatic amino acids, leucine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
134
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(151 citation statements)
references
References 43 publications
13
134
1
2
Order By: Relevance
“…These findings indicate that the direct correlation between Phe and PLA, Tyr and OH-PLA, previously reported for L. lactis subsp. cremoris [11,12], may also be established for L. plantarum ITM21B, since metabolites are produced only in the presence of these amino acids and neither PLA nor OH-PLA are detected in the absence of both amino acids (data not shown). Moreover, the reduction in OH-PLA concentration associated with the increase in PLA level supports the clear correlation observed between the two metabolites ( 1 and Fig.…”
Section: Influence Of Phenylalanine and Tyrosine On Pla Or Oh-pla Biomentioning
confidence: 94%
See 1 more Smart Citation
“…These findings indicate that the direct correlation between Phe and PLA, Tyr and OH-PLA, previously reported for L. lactis subsp. cremoris [11,12], may also be established for L. plantarum ITM21B, since metabolites are produced only in the presence of these amino acids and neither PLA nor OH-PLA are detected in the absence of both amino acids (data not shown). Moreover, the reduction in OH-PLA concentration associated with the increase in PLA level supports the clear correlation observed between the two metabolites ( 1 and Fig.…”
Section: Influence Of Phenylalanine and Tyrosine On Pla Or Oh-pla Biomentioning
confidence: 94%
“…Phenyllactic and hydroxy-phenyllactic acids have also been found as metabolites involved in the formation of cheese flavour and produced by LAB strains through phenylalanine (Phe) and tyrosine (Tyr) degradation, respectively [10][11][12]. In particular, Kieronczyk et al [10] studied the contribution of two lactobacilli (Lactobacillus paracasei and Lactobacillus casei) in the production of carboxylic acids by a Lactococcus lactis subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid catabolism is the final step of proteolysis. In lactic acid bacteria, it is mainly initiated by transamination that converts amino acids into a-keto acids [2][3][4], which are further converted into hydroxyacids or into flavor compounds such as carboxylic acids by an oxidative decarboxylation, or aldehydes by an enzymatic non-oxidative decarboxylation. Conversion of a-keto acids to aldehydes may also be chemically feasible [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Such a catabolic pathway was evidenced in lactococci by 13 C nuclear magnetic resonance (NMR) using [ 13 C]L L -methionine [8]. Other works [9][10][11] have demonstrated that the L Lmethionine transamination in L. lactis is catalysed by two aminotransferases, the aromatic aminotransferase (AraT) and the branched-chain aminotransferase (BcaT). Inactivation of both aminotransferases almost totally prevented the formation of VSCs in a cheese model [12], confirming that this pathway is the main route for VSCs formation by L. lactis.…”
Section: Introductionmentioning
confidence: 99%